2021
DOI: 10.1053/j.jfas.2020.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Fixation Technique for Avulsion Fractures of the Calcaneal Tuberosity

Abstract: Avulsion fractures of the calcaneal tuberosity, although relatively uncommon, occur more frequently in patients with osteoporosis and in the elderly. The results of closed manipulation are poor in these fractures, usually requiring open reduction and internal fixation. However, it is difficult to fix the bone fragment rigidly, because the avulsed bone fragment is small and thin, and the bone quality of the calcaneal body in the elderly is poor. Hence, it is necessary to limit prolonged weight-bearing after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Ninomiya et al [ 15 ] proposed a new technique in which Krackow suture was used to fix avulsed fragments along with Achilles tendon so that the fixation of small or thin fragments can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Ninomiya et al [ 15 ] proposed a new technique in which Krackow suture was used to fix avulsed fragments along with Achilles tendon so that the fixation of small or thin fragments can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,7,12,14,15,[16][17][18]21,22 In terms of fixation, there is no consensus for the optimal construct with various types of fixation techniques being reported in multiple scattered case reports and small series looking at screw fixation techniques with or without augmentation with suture anchors, cerclage/tension band wiring, and plating to improve fixation strength. 1,10,12,13,15,17,19,20,22 Although conventional fixation construct as recommended by OTA/AO utilizes 2 or 3 cortical lag screws inserted perpendicular to the fracture line with bicortical purchase after appropriate reduction, 3 screw fixation alone has been shown to be inadequate to resist the strong Achilles tendon pull in a cadaveric study. 16 Mitchell and colleagues 18 demonstrated 28.2% fracture displacement or implant failure from a cohort of 39 patients treated with screw fixation, whereas Gitajn et al 12 reported 38.5% fixation failure with cannulated lag screws in their review of 33 calcaneal avulsion fractures.…”
Section: Introductionmentioning
confidence: 99%